Pengaruh Financial Leverage, Profitabilitas, Persentase Penawaran Saham Dan Reputasi Underwriter Terhadap Underpricing (Studi Pada Perusahaan Yang Melakukan IPO Tahun 2020-2022) - Ilma, Milla Dunna; Anisah, Nur (Unversitas Islam Madura, 2024)
The purpose of this study is to determine the impact of underpricing of stocks during IPOs on the Indonesian Stock Exchange. This study uses independent variables, namely financial leverage, profitability, share offering ratio, and reputation of underwriter. The population used in this study includes all companies that conducted an IPO on the Indonesia Stock Exchange between 2020 and 2022. The purpose of this study was to examine whether variables such as financial leverage, profitability, share offering ratio, and insurer reputation influence underpricing. The research results show that the profitability of IPOs on the Indonesia Stock Exchange has a negative impact on the undervaluation of stocks from 2020 to 2022, while the proportion of stock offerings has a positive impact on the undervaluation of stocks. On the other hand, the variables financial leverage and underwriter reputation do not affect the underpricing of stocks in IPOs on the Indonesia Stock Exchange from 2020 to 2022.